(untitled) (Research, Society and Development, 2021)
Agricultural practices are a powerful tool with health management contributing to the improved performance of production of animal welfare. The study aimed to verify that farming practices are important tools in the control of bovine mastitis and the degree of knowledge of the producers with respect to the practices. Guided visits were carried out the rural properties, when they were distributed educational materials and tools, made from recyclable material, used in the management of sanitary practices related to animal welfare. To evaluate the physiological profile were collected biological samples such as: blood, feces and milk, and for assessing the sanity and animal welfare were used a questionnaire. Blind 20 cows were selected for a total of 79 rooms of which breast; 36 rooms were negative to the CMT, but 12 were of these were positive to Staphylococcus and microbiology microorganism of higher occurrence. Animal welfare was compromised by the incidence of Subclinical Mastitis, infestation of flies and the absence of prophylactic measures. It is concluded that the use of good agricultural practices is a suitable tool associated with the animal welfare and important in the identification of bovine mastitis, and a lack of information and knowledge regarding best practices, especially in relation to preventive management.